Performance Characteristic of Cold Recycled Mixture with Asphalt Emulsion and Chemical Additives - Shaowen Du (Advances in Materials Science and Engineering)
Three types of chemical additives were used to modify asphalt emulsion recycled mixture. These chemical additives include composite Portland cement (CPC), hydrated lime (HL), and a combination of hydrated lime and ground-granulated blast-furnace slag (GGBF). The influence of different additives on the recycled mixture performance was investigated by volumetric and strength tests, moisture susceptibility test, rutting resistance test, and low temperature bending test. To better understand its performance characteristic, the microstructure images of the recycled mixture were observed by environmental scanning electron microscope (ESEM). Test results demonstrate that the performance improvement of the emulsion recycled mixture depends on the types and content of chemical additives. Several recommendations are presented for the selection of chemical materials. Based on ESEM image analysis, the interface bonding mechanism is proposed to explain the performance characteristic of the recycled mixture with asphalt emulsion and cementitious materials.